Выбор препарата для лекарственной терапии с учетом особенностей субстанции - С. С. Вялов; А. А. Степченко; Т. А. Дронова; Е. В. Винницкая (Архивъ внутренней медицины, 2012)
The article presents current data about the features of the drug production considering substance quality. It was investigated the advantages and disadvantages of various original and generic drugs, include hepatoprotectors. It was discussed and gave recommendations on the tactics of the choice of drug for treatment.